USULAN KERANGKA KEBIJAKAN PENGGUNAAN MEDIA SOSIAL UNTUK PERPUSTAKAAN PERGURUAN TINGGI - Mulatiningsih, Bekti; Johnson, Kelly (BACA: Jurnal Dokumentasi dan Informasi, 2014)
This study provides proposed core elements of social media policy that specifically designed for academic libraries.Evaluation of social media policies from five organisations and a review of the literature were used for data collection.There are 15 proposed core elements recommended: policy objectives; policy definition; scope of the policy;university’s vision and mission; policy users; disclaimer; confidentiality; copyright; privacy; workflow; publicinformation; the use of professional language; the accuracy of the information; rule for links; and university andlibrary’s voices. The results of this study provide important aspects in the development of social media policy. Theproposed core elements of the social media policy discussed in this paper is specifically designed for the academiclibraries, but can also be used for other library types.